2014
DOI: 10.1186/1471-2458-14-957
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of risk behaviour interventions in young men

Abstract: BackgroundYoung adult males commonly engage in risky behaviours placing them at risk of acute and chronic health conditions. The purpose of this scoping review was to provide an overview of existing literature, describing the interventions targeting risk behaviours in young adult males.MethodsA search of seven electronic databases, grey literature and relevant journals reported in English language until May 2013 was conducted. All interventions that promoted healthy behaviours or reductions in risky behaviours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 142 publications
(492 reference statements)
2
33
0
Order By: Relevance
“…Formative research with young men was conducted to identify perceived motivators and barriers for healthy eating and physical activity [17, 35] and to identify their preferences for intervention content and delivery medium [36]. In addition, the program was informed by best practice guidelines for diet [37] and physical activity [38], theoretical guidelines from an integrated framework of Social Cognitive Theory (SCT) [39] and Self Determination Theory (SDT) [40], and evidence from effective health-related interventions in this population [23, 24]. See Additional file 1 for a full list of HEYMAN components and their alignment with the participatory responses from the formative work and with behaviours change strategies from SCT and/or SDT.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Formative research with young men was conducted to identify perceived motivators and barriers for healthy eating and physical activity [17, 35] and to identify their preferences for intervention content and delivery medium [36]. In addition, the program was informed by best practice guidelines for diet [37] and physical activity [38], theoretical guidelines from an integrated framework of Social Cognitive Theory (SCT) [39] and Self Determination Theory (SDT) [40], and evidence from effective health-related interventions in this population [23, 24]. See Additional file 1 for a full list of HEYMAN components and their alignment with the participatory responses from the formative work and with behaviours change strategies from SCT and/or SDT.…”
Section: Methodsmentioning
confidence: 99%
“…Difficulties associated with recruitment and retention may explain why young men are under-represented in health programs and why there is a lack of evidence to guide development of effective health-related interventions for young men [23, 24]. The current evidence base is predominantly made up of health-related interventions that include both sexes [23] and all ages [25, 26], but the heterogeneity in psychological, social, and physical differences between sexes and age groups, highlight the need for gender and age-specific health research and behavioural programs [27].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are systematic reviews in related areas [23,24], neither has had a primary focus on the breadth of consequences for children, and both have more precise foci and mechanistic orientations. Literature searches in MedLine and Google Scholar (October 2014) identified some scoping reviews related to alcohol use [25,26], but none were found on parental drinking's possible harmful effects. This scoping review thus offers the first summary of available evidence from cohort studies of parental drinking and child outcome, both in terms of study characteristics and principal findings.…”
Section: Introductionmentioning
confidence: 99%